Is Stroke Early Supported Discharge still effective in practice? A prospective comparative study. (March 2016) - Fisher, Rebecca J; Cobley, Christine S; Potgieter, Iskra; Moody, Amy; Nouri, Fiona; Gaynor, Catherine; Byrne, Adrian; Walker, Marion F
Objective: Randomised controlled trials have shown the benefits of Early Supported Discharge (ESD) of stroke survivors. Our aim was to evaluate whether ESD is still beneficial when operating in the complex context of frontline healthcare provision. Design: We conducted a cohort study with quasi experimental design. A total of 293 stroke survivors (transfer independently or with assistance of one, identified rehabilitation goals) within two naturally formed groups were recruited from two acute stroke units: 'ESD' n =135 and 'Non ESD' n =158 and 84 caregivers. The 'ESD' group accessed either of two ESD services operating in Nottinghamshire, UK. The 'Non ESD' group experienced standard practices for discharge and onward referral. Outcome measures (primary: Barthel Index) were administered at baseline, 6 weeks, 6 months and 12 months. Results: The ESD group had a significantly shorter length of hospital stay ( P =0.029) and reported significantly higher levels of satisfaction with services received ( P <0.001). Following adjustment for age differences at baseline, participants in the ESD group ( n =71) had significantly higher odds (compared to the Non ESD group, n =85) of being in the ⩾90 Barthel Index category at 6 weeks (OR = 1.557, 95% CI 2.579 to 8.733), 6 months (OR = 1.541, 95% CI 2.617 to 8.340) and 12 months (OR 0.837, 95% CI 1.306 to 4.087) respectively in relation to baseline. Carers of patients accessing ESD services showed significant improvement in mental health scores ( P <0.01). Conclusion: The health benefits of ESD are still evident when evidence based models of these services are implemented in practice.